113 Potential role of coronary physiology in treating 'bystander' disease in patients with ST-elevation myocardial infarction. (17th July 2020) - Knight, Matthew; Rammohan, Vignesh; Preston, Arfah; Williams, Gareth; Ghobrial, Mina; Al Baraikan, Abdulaziz; Gosling, Rebecca; Morris, Paul; Lawford, Patricia; Hose, Rodney; Storey, Robert F; Gunn, Julian
Abstract : Background: Many patients with ST-segment elevation myocardial infarction (STEMI) have non-culprit lesions (NCLs) in other coronary arteries, for which optimal management is uncertain. In the COMPLETE trial, percutaneous coronary intervention (PCI) of eligible NCLs (vessel diameter ≥2.5mm) improved hard clinical outcomes, compared with conservative treatment. However, 99.3% of NCLs were assessed by visualisation of the angiogram using a threshold of ≥70% stenosis, which is an inaccurate method for assessing haemodynamic significance. A pressure wire was used to assess physiological significance (FFR ≤0.80) in only 0.7% of NCLs that visually had 50-69% stenosis. Hypothesis: In the 'real-world', the proportion of STEMI patients with NCL stenoses ≥50% that are of physiological significance, based upon fractional flow reserve (FFR) estimation, is low. Methods: The angiograms of consecutive STEMI patients undergoing primary PCI were retrospectively reviewed by an interventional cardiologist to identify cases that either had NCL stenoses of 50-69% that would have been eligible for COMPLETE if FFR was ≤0.80 or fulfilled the COMPLETE eligibility criteria by visual assessment (stenosis ≥70%). The virtual FFRs of NCLs were computed using the VIRTUheart™ tool. The primary outcome was the proportion of all 'real world' STEMI patients with NCL stenoses ≥50%. Secondary outcomes were a) the proportion of patients with NCL stenoses of 50-69% who had vFFR ≤0.80 ('FFR-guided PCI' group; b) the proportion of NCL stenoses of >70% with a virtual FFR ≤0.80 ('PCI without FFR' group). Results: Angiograms from 248 patients presenting with STEMI and undergoing primary PCI were reviewed. 70 cases (28%), were found with 86 NCLs that would have been potentially suitable for inclusion in COMPLETE (95% CI: 22.4% to 33.6%). Of these 70 cases, 59% of NCLs fell into the 'FFR-guidance' (50-69% stenosis) group and 41% into the 'PCI without FFR' (≥70% stenosis) group. Of the 70, 49 angiograms (70%) were technically suitable for modelling. A positive vFFR was found in 47% of NCLs (95% CI: 33.7% to 60.6%) (see Table 1 ). Conclusion: In a 'real-world' STEMI population, 28% of patients could be considered for either FFR assessment (NCL stenosis 50-69%) or PCI without FFR according to the COMPLETE study criteria. However, of those, nearly 60% should undergo physiological assessment, according to COMPLETE eligibility criteria, even though very few were actually enrolled on this basis. Of the 60%, only 32% were physiologically significant; and, of all the NCLs, only 47% were physiologically significant. Further work is required to determine whether virtual FFR might provide a cost-effective means of identifying patients who will benefit from NCL revascularisation. Conflict of Interest: none